IMPACTO DA REDUÇÃO DE NINHADA DURANTE O PERÍODO LACTACIONAL SOBRE A MORFOFISIOLOGIA MATERNA E SUA REPERCUSSÃO NA PROLE - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Metabolic programming is a phenomenon triggered by nutritional and/ or hormonal changes that occur at critical stages of development, such as lactation and may promote metabolic and functional changes that determine the greater predisposition to pathological conditions in adulthood, as obesity and DM2. The work aims to characterize the effect of reducing the number of offspring pups on the biometric parameters, metabolic and histological maternal and offspring at different stages of lactation.On the 3rd day after birth the number of offspring pups was adjusted Normal Litter (NL), and 9 puppies Reduced Litter (RL), 3 puppies. Mothers and Mothers-NL-RL and the puppies and puppies-NL-RL were studied after 7, 14 and 21 day lactation evaluating the metabolic profile, body composition and histological aspects. The results demonstrated decreased food intake Mother-RL in 3 stages of lactation, higher stock of retroperitoneal fat and increased thermogenic activation in brown adipose tissue (BAT). The mammary gland presented a lower degree of alveolar development with increased adiposity, resulting in milk with higher calorie content. Mothers-RL also show a reduction in the size of pancreatic islets, liver weight reduction with increased blood glucose levels. Puppies-RL had higher body weight, obesity, accompanied by increase in BAT and indications of lower thermogenic activity in this sector. Additionally these animals showed less brain and adrenal weight during the progression of lactation. Puppies-RL also have elevated blood glucose and serum protein. Thus, the study confirms that litter reduction during the lactation period promotes maternal morphophysiological changes with effects on body weight and metabolism of offspring, events that can be programming markers and its complications throughout life.
Keywords: lactação; programação metabólica; mães; prole; lactation; metabolic programming; mothers; offspring; CNPQ::CIENCIAS DA SAUDE